NARRATIVE STUDY OF FULBRIGHT FLTAS’ EXPERIENCES AT A U.S. UNIVERSITY - Labicane, Gianinna Elaine Malapote; Ndebele, Celimpilo; Staruk, Margarita; Febrianti, Dian Suprayitno; Phansriswan, Chayanin; Unal, Suleyman Tugberk; Diouf, Malick Diagne; Nguyen, Ha Anh; Zanca Vega, Sofia (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Transnational mobility programs, such as Fulbright scholarships, offer unique opportunities for academics to engage in scholarly collaboration and gain insights into diverse cultural perspectives. In recent years, more attention has been directed towards the internationalization of education, prompting educators to develop competencies needed to skillfully navigate culturally diverse learning environments.  This research is a qualitative inquiry into the multifaceted experiences of nine (9) Fulbright scholars from the 2022-2023 cohort during their Foreign Language Teaching Assistantship (FLTA) at a private university in the United States of America. Data were collected through semi-structured interviews conducted over video teleconferencing, wherein participants narrated the rewarding and challenging aspects of their experiences during the programs. Transcripts were then subjected to thematic analysis to identify emergent patterns and themes among the participants’ experiences. The findings reveal that the participants viewed student engagement and success, a renewed sense of nationalism, enhanced pedagogical skills, professional growth and impact, and heightened intercultural competence as the rewarding aspects of their experience abroad. However, the participants identified role ambiguity, restricted access to the host university’s resources, and culture shock as the challenges they experienced throughout the duration of the program. These findings emphasize the need for mobility program coordinators and host institutions to strengthen support systems and improve program structures to enhance the quality of international academic experiences. Addressing these issues would allow mobility participants to have more meaningful and impactful engagements, thereby reinforcing the success and ensuring the continuity of transnational academic programs.